Comparison of Knuth Morris Pratt and Boyer Moore algorithms for a web-based dictionary of computer terms - Ali Khumaidi; Yusuf Aras Ronisah; Harjono Padmono Putro (Jurnal Informatika, 2020)
Computer students need a dictionary of computer terms to deepen lectures. In developing dictionary applications, the term computer will choose the fastest and most efficient memory algorithm. The comparison algorithm is Knuth Morris Pratt (KMP) and Boyer Moore (BM) algorithm. Based on previous research, the KMP algorithm has a better performance compared to other string matching algorithms. However, other studies have concluded that the BM algorithm has better performance. Besides, the Zhu-Takaoka algorithm is more efficient than the KMP algorithm in dictionary development. The BM algorithm has the same search concept as the Zhu-Takaoka algorithm. The determination of the fastest and most efficient algorithm in this study uses the Exponential Comparison Method (ECM). ECM sets criteria for when searching and using the memory in the search process. The results of the comparison of the KMP and BM algorithm are the search time for the BM algorithm is 37.9%, and the KMP algorithm is 62.1%. The results of the use of search memory for the KMP algorithm are 50.6%, and the BM algorithm is 49.4%. The total ECM score shows that the BM algorithm is 0.55% better than the KMP algorithm.